2020
DOI: 10.3390/ijerph17197336
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Approach Limiting Extractions under General Anesthesia Could Improve Oral Health

Abstract: Access to dental treatment could be difficult for some patients due to dental phobia or anxiety, cognitive or sensorial disabilities, systemic disorders, or social difficulties. General anesthesia (GA) was often indicated for dental surgery, and there is almost no available data on adapted procedures and materials that can be applied during GA for maintaining functional teeth on the arches and limiting oral dysfunctions. This study evaluates changes in oral health-related quality of life and mastication in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Aside from these recommendations, this study indicates a need to address prevailing beliefs around DGA and what is possible therewith. Modern research advocates for non-extraction approaches under DGA to improve function and quality of life 43 and emphasizes the safety of DGA. 33 As part of this change in perceptions, the definitions of success and failure of dental treatment under GA need to be redefined.…”
Section: Clinical Educational and Research Implications (Recommendations)mentioning
confidence: 99%
“…Aside from these recommendations, this study indicates a need to address prevailing beliefs around DGA and what is possible therewith. Modern research advocates for non-extraction approaches under DGA to improve function and quality of life 43 and emphasizes the safety of DGA. 33 As part of this change in perceptions, the definitions of success and failure of dental treatment under GA need to be redefined.…”
Section: Clinical Educational and Research Implications (Recommendations)mentioning
confidence: 99%
“…Another limit of the current study is that occlusal adaptation could not be evaluated, as solely radiological criteria were used. SSCs are chosen as the restoration of choice for placement in special circumstances by our team because it is assumed that they restore dental function, i.e., that they maintain chewing function and provide a stable occlusion for swallowing [ 18 , 30 ]. A previous cohort study demonstrated that a comprehensive restorative approach, including SSC placement for permanent molars, helped to increase chewing activity and oral health-related quality of life following rehabilitation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…SSCs are chosen as the restoration of choice for placement in special circumstances by our team because it is assumed that they restore dental function, i.e., that they maintain chewing function and provide a stable occlusion for swallowing [ 18 , 30 ]. A previous cohort study demonstrated that a comprehensive restorative approach, including SSC placement for permanent molars, helped to increase chewing activity and oral health-related quality of life following rehabilitation [ 18 ]. The current results are also in accordance with a recent, large-scale study, which concluded that SSCs are a durable treatment option for the restoration of the severely carious posterior permanent dentition, in the context of GA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations